The B Word : Bisexuality in Contemporary Film and Television - San Filippo, Maria (Book collections on Project MUSE., 2013)
Often disguised in public discourse by terms like "gay," "homoerotic," "homosocial," or "queer," bisexuality is often absent from queer studies and virtually untreated in film and media criticism. The author aims to explore the central role bisexuality plays in contemporary screen culture, establishing its importance in representation, marketing, and spectatorship. By examining a variety of media genres including art cinema, sexploitation movies, vampire films, "bromances," and series television, the author discovers "missed moments" where bisexual readings of these texts reveal a more malleable notion of subjectivity and eroticism.